2013
DOI: 10.1159/000354747
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Interventions for Social Anxiety Disorder - an Overview

Abstract: Internet-based interventions hold specific advantages and disadvantages in the treatment of social anxiety disorder (SAD). The present review examines different approaches in the internet-based treatment of SAD and reviews their efficacy and effectiveness. 21 studies investigated the potential of guided and unguided internet-based cognitive-behavioral treatments (ICBT) for SAD, comprising a total of N = 1,801 socially anxious individuals. The large majority of these trials reported substantial reductions of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 78 publications
2
39
0
Order By: Relevance
“…Although there is a wealth of studies that show the efficacy and effectiveness of Internet-based cognitive behavioral therapy (ICBT) in Western countries, there is a considerable lack of studies that investigate the efficacy of such treatments in non-Western countries [2]. So far, several studies have evaluated the efficacy of ICBT for SAD in controlled trials in Western countries with promising results [3]. An important discussion in the field is about the degree of support and guidance needed during Internet-based self-help treatments [4].…”
Section: Figmentioning
confidence: 99%
“…Although there is a wealth of studies that show the efficacy and effectiveness of Internet-based cognitive behavioral therapy (ICBT) in Western countries, there is a considerable lack of studies that investigate the efficacy of such treatments in non-Western countries [2]. So far, several studies have evaluated the efficacy of ICBT for SAD in controlled trials in Western countries with promising results [3]. An important discussion in the field is about the degree of support and guidance needed during Internet-based self-help treatments [4].…”
Section: Figmentioning
confidence: 99%
“…In the last decade, Internet-based cognitive behavior therapy (ICBT) for SAD, which is a highly promising approach to increasing accessibility and availability to treatment, has been developed and validated in Western countries [9][10][11] as well as in China [12]. SAD is one of the disorders for which ICBT has the strongest empirical support [13,14]. However, a substantial proportion of patients do not achieve clinically significant improvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, a substantial proportion of patients do not achieve clinically significant improvement. In studies on ICBT for SAD, clinically significant change rates range between 40-60%, which means approximately half of the participants did not achieve significant improvements [14]. The few studies on predictors of treatment outcomes in ICBT for SAD yielded inconsistent findings [13].…”
Section: Introductionmentioning
confidence: 99%
“…Research consistently suggests that web-based interventions for SAD can significantly improve social anxiety symptoms (Boettcher, Carlbring, et al, 2013). Trials directly comparing ICBT with face-to-face therapy have revealed that both treatment conditions made large and similar improvements (e.g.…”
mentioning
confidence: 99%